Excited states in dye-based functional materials - Kondratenko, P.A.; Lopatkin, Yu.M.; Sakun, T.N. (Functional Materials, 2008)
Results of experimental and theoretical studies are considered concerning the processes running during a molecule relaxation from a high-excited state obtained both under a single-quantum (S₀->Sn) and a two-stage (S0 -ʰᵛ> S₁ -> T₁ -ʰᵛ> Tn) excitation. Polymeric layers containing dyes (resazurin, methylene blue, and brilliant green) have been used as the study objects. It has been established that in high-excited states the systems may live during several vibrations characterizing the specified states. The dissociative states have been shown to exist among the high-excited ones. This causes the quasi-equilibrium molecular dissociation processes, electron transfer between the high-excited molecule and its surrounding (matrix), etc., proceeding from those states. Such processes cause the dye fading on textiles, the dye instability in the course of laser radiation, etc. The dye photo-induced instability has been proposed to make use for information storage .